A Novel Regenerative Approach for Acne Vulgaris Using Combined Umbilical Cord Mesenchymal Stem Cell-Derived Secretome and Platelet-Rich Plasma: A Case Report - Zamzam, Salsabillah; Kusumaningrum, Novi; Prawitasari, Salindri; Cahyani, Dini; Adityani, Resanti (International Journal of Cell and Biomedical Science, 2025)
Background: Acne vulgaris is a chronic inflammatory skin disorder that often leads to scarring and pigmentation. Conventional therapies may provide limited improvement and are frequently associated with adverse effects. Recent advances in regenerative medicine suggest that stem cell–derived secretome and platelet-rich plasma (PRP) may promote skin repair and rejuvenation through anti-inflammatory and regenerative pathways. Case Presentation: A 21-year-old male presented with persistent inflammatory acne and post-acne hyperpigmentation. The patient underwent two sessions of combined SH-MSCs-derived secretome and PRP therapy at two-week intervals. Facial assessments were performed using the Janus Skin Analyzer at baseline, day 14, and day 28. Quantitative analysis revealed significant improvement in multiple parameters, including reduction of pore size, pigmentation index, and sebum levels, accompanied by enhanced skin elasticity. Clinically, the patient exhibited visible improvement in overall skin texture, evenness, and clarity without any adverse reactions. Results: Marked clinical improvement was observed after the second session, with visible reduction in acne lesions, fading of post-acne marks, and overall improvement in skin radiance. Quantitative analysis demonstrated a 30% reduction in pore condition, 58% increase in elasticity, 35% decrease in pigmentation index, and 227% reduction in sebum levels compared to baseline. These findings indicate significant enhancement in skin texture, tone, and elasticity. Conclusion: Combination therapy using SH-MSCs-derived secretome and PRP demonstrated promising regenerative and aesthetic outcomes in this patient with acne vulgaris. Larger-scale clinical studies are warranted to validate efficacy and optimize treatment protocols.